Hiperadrenocorticismo em cães: revisão - Romão, Felipe Gazza; Leitão, Luciene Maria Martinello; Machado, Luiz Henrique de Araújo [UNESP]; Lourenço, Maria Lúcia Gomes; Mamprim, Maria Jaqueline [UNESP]; Heckler, Marta Cristina Thomas; Doiche, Danuta Pulz (My University, 2011)
Hyperadrenocorticism is a relatively common endocrinopathy in dogs, which is associated to an excessive production or administration of cortisol. The most affected breeds are Poodles, Teckels, Boxers, Boston Terriers and Beagles. The clinical signs most commonly observed are polyuria, polydipsia, polyfagia, panting, distended abdomen, endocrine alopecia, muscular weakness and lethargy. Laboratorial abnormalities include stress leukogram, increase in alkaline phosphatase and alanine aminotransferase activities, hypercholesterolemia, lipemia, hyperglycemia and hyposthenuria. The preferred essay to evaluate adrenal gland function is the low-dose dexamethasone suppression test, whereas the most used treatments include mitotane and trilostane. The objective of this paper is to review hyperadrenocorticism in dogs, because this disease is relatively common in small animal clinics and has many long-term complications.

El hiperadrenocorticismo es una endocrinopatía común en perros asociada con la producción o administración excesiva de cortisol. Las razas más comúnmente afectadas son Poodles, Teckels, Boxers, Boston Terriers y Beagles. Los signos clínicos observados son: poliuria, polidipsia, polifagia, respiración jadeante, distensión abdominal, alopecia endocrina, debilidad muscular y letargia. Los hallazgos de laboratorio se caracterizan por leucograma de estrés, aumento de la actividad de la fosfatasa alcalina y alanina aminotransferasa, hipercolesterolemia, hiperlipemia, hiperglucemia y hipostenuria. El examen de elección para evaluación de la función de la glándula adrenal es la supresión de la dexametasona en dosis bajas, y los tratamientos más comunes son las terapias con mitotano y trilostano. El objetivo de este trabajo es examinar el hiperadrenocorticismo en perros, porque es una enfermedad relativamente común en la clínica de pequeños animales que tiene muchas complicaciones a largo plazo.

O hiperadrenocorticismo é uma endocrinopatia comum em cães, associada à produção ou à administração excessiva de cortisol. As raças mais comumente acometidas são poodle, teckel, boxer, boston terrier e beagle. Os sinais clínicos mais comumente observados são: poliúria, polidipsia, polifagia, respiração ofegante, abdômen distendido, alopecia endócrina, fraqueza muscular e letargia. Os achados laboratoriais caracterizam-se por leucograma de estresse, aumento da atividade da fosfatase alcalina e da alanina aminotransferase, hipercolesterolemia, lipemia, hiperglicemia e hipostenúria. O teste de escolha para avaliação da função da glândula adrenal é a supressão pela dexametasona em dose baixa, e os tratamentos mais utilizados são as terapias com o mitotano e o trilostano. O objetivo deste trabalho é fazer uma revisão sobre hiperadrenocorticismo em cães, por se tratar de enfermidade relativamente comum na clínica de pequenos animais e com diversas complicações a longo prazo.
Hyperadrenocorticism in dogs: review
Hiperadrenocorticismo en perros: revisión
Keywords: Adrenal; Dexamethasone suppression test; Mitotane; Adrenal; Teste de supresión de la dexametasona, mitotano; Adrenal; Supressão por dexametasona; Mitotano